"Situated Bystandership" During and After the Rwandan Genocide. Issue 1 (2nd January 2018) - Donà, Giorgia
ABSTRACT: The dominant account of the Rwandan genocide and its aftermath focuses on victims and perpetrators, and rescapés and génocidaires . Less is known about bystanders, mainly Hutu non-perpetrators, who are held collectively responsible for having witnessed violence without trying to stop the killers or help the victims. This article challenges the homogenous portrayal of the unresponsive bystander group, and introduces the novel concept of "situated bystandership" to draw attention to the proximal and representational contexts that shape bystanders' responses, roles and positions in society. First, to be a "situated bystander" means to resist the pressure to participate in genocidal violence and to belong to a moral order that is distinct from that of the extremists: the moral world of the ordinary, good-hearted people. Second, Rwandans who are "neither pursuing nor being pursued" occupy multiple roles at different points in time. Many are bystanders to specific episodes of violence and their "acts of non-intervention" shape the course of history. Given the pressure to participate in the genocide, the inaction of bystanders could be considered as passive resistance to the ideology of mass killing. Therefore, in a continuum between victims and perpetrators, bystanders might be positioned closer to the victims than the perpetrators. Third, gacaca is a process through which not only is culpability ascertained but individual innocence is also established. This reconfiguration makes it possible to shift the homogenized perception of Hutu non-perpetrators from the position of the morally guilty bystander group towards that of the individual innocent bystander. In contrast to the tendency to essentialize accounts of violence, homogenize groups and reframe controversial stories to fit political strategies, there is value in standing back and identifying the contexts that shape bystanders' roles, responses and representations. "Situated bystandership" is a lens through which this objective can be achieved.